MENTAL ACCOUNTING BIAS TERHADAP PERILAKU KEUANGAN: SYSTEMATIC LITERATURE REVIEW - Ignatz Novrian Fayliencent; Ferdinando Solissa; Margaretha Turor; Putu Anggreyani Widya Astuti (Jurnal Akuntansi Dan Manajemen, 2025)
This study aims to analyze the phenomenon of mental accounting bias and its implications for individual financial behavior through a systematic literature review (SLR) approach. A total of nine Scopus-indexed articles were reviewed to identify how mental accounting influences financial decisions in contexts such as investment, consumption, and personal money management. The results reveal that mental accounting bias significantly affects non-rational decision-making by leading individuals to categorize money into separate mental accounts that shape perceptions of risk, gain, and loss. In investment decisions, mental accounting causes investors to divide their portfolios based on emotional preferences rather than economic efficiency, while in consumption behavior, the house-money effect encourages higher spending of windfall income. Furthermore, the use of digital technologies such as smartphone applications has been found effective in mitigating this bias by increasing transaction salience and financial awareness. Theoretically, this research reinforces Prospect Theory (Kahneman & Tversky, 1979) and Financial Behavior Theory (Shefrin & Statman, 2000), emphasizing that financial decisions are influenced not only by rational factors but also by psychological and emotional processes. Practically, the study highlights the importance of behavioral financial literacy and technology utilization in reducing cognitive bias and promoting wiser financial management.